(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article is devoted to the problems of adapting strategic management tools to the rapidly changing external environment caused by the rapid development of the digital economy and its impact on international business. In this article, the main trends of changing the digital business environment at the macro and micro level, the issues of increasing the efficiency of using the internal potential of the company, the specific features of the competitive struggle based on the active use of information and communication technologies are covered.